2021
DOI: 10.1007/s11469-020-00477-9
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Depression: A Comparative Study Among the General Population and Healthcare Professionals During COVID-19 Pandemic Crisis in Bangladesh

Abstract: The COVID-19 pandemic affects individuals’ mental health that can result in fear of getting COVID-19 infection and depression. As there is no prior study available, we evaluated these mental health outcomes and associated factors among the general population and healthcare professionals (HCPs) in Bangladesh. This nationwide cross-sectional study comprised 3388 individuals including 834 HCPs. The measures included socio-demographics, healthcare, and patient-care related information, the Bangla Patient Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 34 publications
7
95
1
5
Order By: Relevance
“…Studies show an association of depression with fear of infection, distress and loss of quality sleep. 18,23,33,40 Fear of COVID-19 is positively correlated with psychological distress (p=0.638**, p<0.001) as well as insomnia (p=0.444**, p<0.001) which is also observed in similar studies. 18,22,25,29 The Kessler psychological distress scale is positively correlated with ISI (p=0.741%**, p<0.001).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Studies show an association of depression with fear of infection, distress and loss of quality sleep. 18,23,33,40 Fear of COVID-19 is positively correlated with psychological distress (p=0.638**, p<0.001) as well as insomnia (p=0.444**, p<0.001) which is also observed in similar studies. 18,22,25,29 The Kessler psychological distress scale is positively correlated with ISI (p=0.741%**, p<0.001).…”
Section: Discussionsupporting
confidence: 74%
“…32 A study on healthcare workers in Bangladesh suggested that females had a higher fear of COVID-19 and higher depression features as a result. 33 Another study on the doctors and postgraduate trainees in Pakistan highlighted the fear of COVID-19 was significantly higher in female postgraduate trainees, doctors who had less than 5 years of experience along with high levels of workplace phobia, panic, anxiety and work avoidance behaviours. 34 Spearman correlation was used to analyze the association between different groups.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there was no published report regarding the integration of online education, FAD, and subsequent psychological distress among university students in Bangladesh rather than several studies on psychological distress among the general population [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and medical professionals [ 47 , 48 , 49 ]. However, only a nearly alike study is available online conducted on intermediate college students in Bangladesh [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 During disease outbreaks, frontline healthcare workers are vulnerable to temporary and long-term psychological issues due to the fears of disease contraction and being quarantined, the possibility of their family and friends being infected, caring for fellow workers as a patient, feelings of stigmatization, and rejection by others in their locality. 5,6 Predominantly, the psychological issues confronting the HCWs include high levels of depression, fear, anxiety, insomnia, and distress. 7 Suicide has been stated as a severe psychological consequence of COVID-19.…”
Section: Introductionmentioning
confidence: 99%